BPAs probability-based clearance buffers. I. General development. - Reding, J.L (IEEE Transactions on power delivery)
When designing new lines or analyzing existing lines, most utilities add a mechanical clearance buffer to regulatory clearance requirements. This clearance buffer accounts for systematic and random variations in field clearances about a design clearance. This long recognized and expected variation in field clearance is generally treated by utilities with an arbitrary and deterministic clearance buffer. Such treatment was also the Bonneville Power Administration's common practice until 1979 when a probabilistic approach to the clearance buffer was developed. The probabilistic clearance buffer assigns acceptable assurance levels to meet National Electrical Safety Code clearances in the field and is based on statistical predictor models. A general statistical clearance model is developed with various measurements and construction practices influencing the model being discussed. The general statistical clearance model is used to develop probabilistic clearance buffers for the design of new lines, and the analysis of existing lines, which met regulatory clearances in the field at any prescribed assurance level.